Complicated ruptured mycotic intracerebral emboli from infective endocarditis presenting like meningoencephalitis - Norhayati R,; Afliza Abu Bakar,; Dazlin MS,; Ida ZZ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Infective endocarditis (IE) is a potentially life-threatening disease which carries high risk of morbidity and mortality. The variability of clinical presentation of infective IE remains a diagnostic challenge for the Emergency Physicians. The clinical manifestation may present as an acute, rapidly progressive infection with the absence of classical immunological vascular phenomenon or as subacute or chronic disease with vague constitutional symptoms that may mislead initial assessment and mimic other conditions. Symptoms may also manifest as a result of systemic embolization which can be catastrophic and life-threatening especially if it ends up in the cerebral circulation. IE complicated by cerebral mycotic aneurysm (CMA) is the worst neurological sequalae and can be misdiagnosed as a primary intracranial infection such as meningoencephalitis. Here, we report a case of neurological emergency secondary to systemic embolization of IE with a devastating diagnosis of CMA. History of prolonged fever associated with headache and focal neurological deficit led to the initial diagnosis of meningoencephalitis due to a low clinical suspicion of the disease in the Emergency Department. In emergency setting, a combination of high degree of clinical suspicion together with thorough history, physical examination and diagnostic imaging are crucial in order to guide and establish the diagnosis of this potentially devastating disease. Early recognition and initiation of aggressive treatment is crucial to provide better prognosis and higher survival rate for patients with CMA.